Comparison of Paliperidone Palmitate from Different Crystallization Processes and Effect on Formulations In Vitro and In Vivo - Junfeng Shi; Dan Wang; Yang Tian; Zengming Wang; Jing Gao; Nan Liu; Xiang Gao; Aiping Zheng; Hui Zhang; Meixian Xiang (MDPI AG, 2022)
The quality of active pharmaceutical ingredients (APIs) is an important factor which can affect the safety and efficacy of pharmaceuticals. This study was designed to investigate the nature of paliperidone palmitate (PP) obtained by different crystallization processes, then compare the characteristics between test formulations which prepared PP of different crystallization and reference formulations (Invega Sustenna®) in vitro and in vivo. Two different PPs, namely PP-1 and PP-2, were prepared by different crystallization methods. Contact angle, morphology, and crystallinity of the PPs were characterized. Taking the particle sizes and distribution of Invega Sustenna® as reference, test formulations were prepared by the wet milling method using either a PP-1 or PP-2 sample. Their release behavior, stability in vitro, and pharmacokinetics in vivo were subsequently investigated. The results indicated that PP-2 had a higher surface free energy (SFE). More small particles were attached to the PP-1 surface under the influence of crystallization temperature. Different crystallization processes did not change the crystal of PP, but changed the crystallinity of PP. There was no obvious difference in in vitro releases between test formulations. However, the stability and state of formulation containing PP-2 were better compared to formulations containing PP-1, indicated by differences in crystallinity and SFE. Meanwhile, pharmacokinetic in vivo results demonstrated that the pharmacokinetic profiles and parameters of formulation containing PP-2 and Invega Sustenna® tended to be consistent, but those of formulations containing PP-1 were significantly different from those of formulations containing PP-2 or Invega Sustenna®, and there was burst release phenomenon of formulations containing PP-1 in rats. PP made by different crystallization processes could induce changes in appearance, SFE, and crystallinity, and further affect the stability, state, and pharmacokinetic in vivo formulation.